2019
DOI: 10.1051/0004-6361/201834525
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stars stripped in binaries on the integrated spectra of stellar populations

Abstract: Stars stripped of their envelopes from interaction with a binary companion emit a significant fraction of their radiation as ionizing photons. They are potentially important stellar sources of ionizing radiation, however, they are still often neglected in spectral synthesis simulations or simulations of stellar feedback. In anticipating the large datasets of galaxy spectra from the upcoming James Webb Space Telescope, we modeled the radiative contribution from stripped stars by using detailed evolutionary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 184 publications
(247 reference statements)
2
120
2
Order By: Relevance
“…Assuming a 0.2 Z e metallicity, Chabrier IMF (Chabrier 2003), and Padova isochrone (Bertelli et al 1994;Bressan et al 1993;Fagotto et al 1994), we find that these models produce log(x ion ) values within 25-25.2. When including the effect of stripped, binary stars in the BPASS (Eldridge et al 2017) and Starburst99 (Götberg et al 2019) single-star models, we find only a small, ∼5%, enhancement to x ion . This is because these stripped, binary stars emit H I-ionizing photons at a rate that is 5% of the rate of H I-ionizing photons emitted by the massive single O-type stars (Götberg et al 2019).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Assuming a 0.2 Z e metallicity, Chabrier IMF (Chabrier 2003), and Padova isochrone (Bertelli et al 1994;Bressan et al 1993;Fagotto et al 1994), we find that these models produce log(x ion ) values within 25-25.2. When including the effect of stripped, binary stars in the BPASS (Eldridge et al 2017) and Starburst99 (Götberg et al 2019) single-star models, we find only a small, ∼5%, enhancement to x ion . This is because these stripped, binary stars emit H I-ionizing photons at a rate that is 5% of the rate of H I-ionizing photons emitted by the massive single O-type stars (Götberg et al 2019).…”
Section: Discussionmentioning
confidence: 79%
“…When including the effect of stripped, binary stars in the BPASS (Eldridge et al 2017) and Starburst99 (Götberg et al 2019) single-star models, we find only a small, ∼5%, enhancement to x ion . This is because these stripped, binary stars emit H I-ionizing photons at a rate that is 5% of the rate of H I-ionizing photons emitted by the massive single O-type stars (Götberg et al 2019). As a result, when a constant star formation history is assumed, the emission from the massive single stars always dominates the emission from other less massive stripped, binary stars.…”
Section: Discussionmentioning
confidence: 79%
“…z ∼ 0 (e.g., Kewley et al 2001;Senchyna et al 2017) and z ∼ 2 − 4 (e.g., Nanayakkara et al 2019) studies have shown that stellar population models may lack mechanisms that produce high energy photons in the EUV, which are required to produce observed emission line ratios such as [Sii]λ6717λ6731/Hα and observed He ii λ1640 spectral features (also see Section 5.3 of Kewley et al 2019 for a detailed discussion on current limitations of stellar populations models). Including effects of X-ray binaries (e.g., Schaerer et al 2019) and stripped stars (e.g., Götberg et al 2019) in stellar population synthesis models have shown to in-crease the production of ionizing photons. Therefore, self consistent treatment of stellar evolution with rotation and binaries that contribute to such phenomena are crucial to make strong constraints on the nature of stellar populations in high-z galaxies.…”
Section: Expectation From Current Stellar Population Modelsmentioning
confidence: 99%
“…Significant work developing models for the response of stars to binary mass transfer has been carried out by a variety of teams [6,11,46,[114][115][116]. Very recently, a small grid of atmospheres for stars which have had their envelopes stripped in a binary interaction have been incorporated in a stellar population synthesis by Starburst99 [117]. However, perhaps the most influential binary synthesis models in recent years have been the products of the Binary Population and Spectral Synthesis (BPASS) project [6,11,46,59,118].…”
Section: Improved Stellar Modelsmentioning
confidence: 99%
“…One focus of recent attention, particularly in the high redshift universe where stellar populations <100 million years old are more common, has been improved models for the spectra of stripped, helium-dominated star atmospheres. While either giant Wolf-Rayet stars [123][124][125][126] or naked helium dwarfs [117,127,128] may result from extreme wind-driven mass loss in single stars, they result in larger numbers from binary interactions and incorporation of these atmospheres can make significant differences to the ultraviolet spectrum of composite binary stellar populations. To a large extent, the production and survival of these extreme objects is dependent on the rate at which stars lose their mass through stellar winds [129,130].…”
Section: Improved Atmospheresmentioning
confidence: 99%